Development of low profile unidirectional antenna for wireless local area network application - Abdulrazak, Lway Faisal (2007)
This thesis will review the project conducted the development of a low profile unidirectional antenna for WLAN applications, performed with frequency range 2.4-2.4835GHz. The Radial Waveguide Slot Array Antenna (RWSA) is investigated as a low profile, significant shape, lightly weight, simple but effective, easy to design and fabricate with reasonable cost efficient. Simulation and optimization of structure based on Zeland Fidelity - FDTD (Finite-Difference Time-Domain) with Full-3D EM Simulation for the radiation pattern, and return loss. The other part of this project deals with producing design relying on optimum simulation results. The developed antenna was tested in terms of return loss, gain and radiation pattern. Finally, integrated experimental trial had been compared with a monopole antenna on an Access point for WLAN. Measurements are conformed to results presented by the prototype simulation